2021
DOI: 10.21675/2357-707x.2021.v12.n7.supl.1.5209
|View full text |Cite
|
Sign up to set email alerts
|

Inserção de Dispositivo Intrauterino por Enfermeiros da Atenção Primária à Saúde

Abstract: RESUMOObjetivo: descrever a vivência de enfermeiros na implementação do serviço de inserção de dispositivo intrauterino de cobre na Atenção Primária à Saúde de Florianópolis, Santa Catarina. Método: relato de experiência apresentando as seguintes etapas: (a) elaboração de material teórico-prático; (b) formação de enfermeiros facilitadores; e (c) monitoramento e avaliação do processo. Resultados: no total, foram habilitados 115 enfermeiros, entre profissionais efetivos e residentes. Quanto à ampliação do acesso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
11

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 0 publications
0
8
0
11
Order By: Relevance
“…From the analysis of studies ( 15 , 24 - 32 ) , three categories emerged: Nurse training to insert an intrauterine device; Nurses’ competency to insert an intrauterine device; and Women’s access to intrauterine devices.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the analysis of studies ( 15 , 24 - 32 ) , three categories emerged: Nurse training to insert an intrauterine device; Nurses’ competency to insert an intrauterine device; and Women’s access to intrauterine devices.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the competency of nurses to insert IUD, mentioned in the studies, it is highlighted that, upon acquiring it, nurses can positively influence the reproductive planning of adult and adolescent women, qualification of care, in addition to enabling training other nurses ( 15 , 26 , 28 , 30 ) , an aspect also considered an attribute of APN ( 35 ) , overcoming hegemonic models and physician-centered ( 15 , 26 , 28 , 30 ) . Research carried out in England, published in 1999, already revealed favorable evidence in this regard, highlighting that trained nurses perform efficient and safe IUD insertions, regardless of patients’ age, in addition to a better cost-benefit ratio ( 13 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A oferta de inserção do DIU de cobre TCu 380A, no contexto da consulta de enfermagem, quando realizada com embasamento científico e capacitação técnica, configura-se como uma ferramenta potente para a democratização do acesso a esse método contraceptivo de longa duração (22). Dados do DATASUS mostram que o enfermeiro da Atenção Primária é a categoria da enfermagem que mais inseriu DIU de cobre entre 2020-2021, com cerca de 1.381 inserções, ficando à frente de enfermeiros obstétricos (1.006 inserções) e generalistas (885 inserções) (23).…”
Section: Discussionunclassified